Locomotive No. 5320, "President Cleveland," of the Baltimore and Ohio, which heads the railroad's Air-Conditioned train exhibited at A Century of Progress, Chicago, 1934
President Cleveland,"" of the Baltimore and Ohio Railroad, which heads the Air-Conditioned train at A Century of Progress, Chicago 1934. This is one of twenty-one similar type locomotives of the ""President"" series, which haul the Capitol Limited, the National Limited, the Columbian and other B. & O. passenger trains.